Survei Profil Kondisi Fisik Kekuatan, Kecepatan & Daya Tahan U-14 (Survei pada Pemain SSB Bina Muda Juwana Pati Tahun 2021) - Mahmudi, Deny Ali; Irawan, Ricko (Universitas Negeri Semarang, 2023)
This study aims to determine the level of physical condition of strength, speed, and endurance in athletes in the age group of 14 SSB Bina Muda Juwana Pati in 2021. This study used a survey method with a quantitative research type with a descriptive approach. The research sample was athletes at SSB Bina Muda Juwana with a total of 20 athletes in the age group of 14 years. The research instrument used measurements of speed (sprinting 40 meters), Strength (Push Ups and Sit Ups 2 minutes), endurance (12 Minutes Run). The data analysis technique used is descriptive percentage. The results of the research conducted by researchers on the physical condition of strength with Sit Up exercises which obtained good results, and Push Up exercises which obtained moderate results. The physical condition of speed got the overall result that the speed level seen from the 50 meter running exercise was in the very good category. The physical condition of endurance as measured by running exercises with a distance of 2.4 Km then calculated the time obtained for the players to get the results into the good category. The conclusions in this study, it can be concluded that the physical condition of strength in the 14 year age group at SSB Bina Muda Juwana Pati in 2021 is categorized as good.